Packaging as a tool to improve the shelf life of poultry meat. (September 2019) - Baltic, T; Ciric, J; Brankovic Lazic, I; Ljubojevic Pelic, D; Mitrovic, R; Djordjevic, V; Parunovic, N
Abstract: In this paper, recent findings about poultry meat spoilage and packaging systems are discussed. Poultry meat is widely consumed and its consumption has been growing for decades. Raw poultry meat is a highly perishable food with short-term shelf life, and thus, novel strategies for maintaining safety and quality must be applied to meet the demands of the modern consumer. The main cause of meat spoilage is bacterial growth and the goal of this paper is to highlight the importance of GHP ( Good Hygiene Practice ) in the chain of processing, packaging, storage, and distribution of poultry meat in order to avoid economic losses and meet consumer expectations.